MODERN COMBINED TREATMENT OF LUNG ABSCESSES IN DIABETIC PATIENTS: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Khamdamov, Sh.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The standard treatment for lung abscess consists of systemic antibacterial therapy, which is based on the suspected or proven bacterial spectrum of the abscess. Secondary abscesses, despite targeted antimicrobial therapy, are associated with a poor prognosis, which depends on the general condition of the patient and the underlying disease; lethality reaches 75%. Negative prognostic factors are old age, severe concomitant diseases, immunity suppression, bronchial obstruction and neoplasms. Surgical intervention due to the failure of conservative treatment is required only in 10% of patients, while the probability of success reaches 90%, and postoperative mortality ranges from 0 to 33%. The success of treatment after percutaneous drainage is achieved in 73-100% of cases with an acceptable (0-9%) mortality rate. Treatment of lung abscesses requires an integrated approach consisting of local (vacuum aspiration of the cavity contents) and in general (a combination of several antibiotics, infusions of general strengthening and protein preparations).